(untitled) (International Seven Journal of Health Research, 2024)
The present article aims to evaluate the risk of falls in elderly people with Alzheimer’s through the times up and go (tug), anterior functional range (TAF), and berg balance scale (eeb) tests. Introduction: morphological, functional, biochemical and psychological changes occur in the aging process. Alzheimer’s pathology affects about 27 million people, who are over 65 years of age. It is a neurodegenerative disorder that progressively compromises the performance of your daily activities. Elderly people affected by this pathology have cognitive impairment that doubles their chances of falling, compared to elderly people who have conserved cognition. The methodological approach applied to the development of this work consisted of conducting a bibliographic review of the integrative literature in databases recognized by the scientific community, such as Electronic Library Online (SciELO), Latin American and Caribbean Health Sciences Literature (LILACS) and Google Scholar. The search was restricted to publications in the period from 2019 to 2024, in Portuguese. The evaluation, in turn, is of paramount importance to assess what are the risk factors that lead the elderly to fall. Functional tests are essential at this time of patient evaluation.